Attributes of The Supervisory Board In Enhancing Innovation Performance - Desi ilona; Desi Permata Sari; Messy Wisandra; Zaitul Zaitul (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Supervisory board’s attribute as determinants of innovation performance has been investigated by previous research using a one-tier board system, such as in the US and UK. There is limited evidence in such a study in continental European corporate governance systems, such as Indonesia. A study using data from Indonesia with a unique two-tier board system may enrich the corporate governance literature. This study explores the supervisory board’s attributes in enhancing a company's innovation performance by using gender, tenure, and foreigners. The agency theory is applied to this study. The purposive sampling method was used to obtain data from 222 companies listed on IDX from 2014-2018. Using multivariate analysis, the result showed that gender and foreign supervisory board have no significant impact in enhancing better Company's innovation, with the ability to create better performance. However, the supervisory board's tenure has a significant positive relationship with innovation performance. Hence, the company size negatively influences innovation performance. This study has practical and theoretical implications, and they discuss in detail in the paper.